Analisis Lagu Karo “Erkata Bedil” Karya Djaga Sembiriing Depari Menggunakan Pendekatan Ekspresif - Puspita, Diana; Reza Pahlevi Ginting (Literasi: Jurnal Pendidikan Guru Indonesia, 2024)
A song is a work of art which is the result of the relationship between sound art and language art. Songs are created to convey messages and express what the songwriter feels and sees. In this increasingly developing era, many young Karo people are leaving behind their cultural heritage such as dance, music, especially traditional songs from the land of Karo. Therefore, in this research the author anan carried out an analysis of one of the Karo struggle songs entitled "Erkata Bedil by Djaga Sembiring Depari, and explained the meaning of the song for the Karo tribe community. In this research, the author used a qualitative method with a pragmatic approach. This song is often sung or performed when commemorating the "guro-guro aron drum (traditional party for young people after the harvest is over). This song has a very strong meaning in the struggle for independence carried out by the heroes.